2014
DOI: 10.1080/03650340.2014.933811
|View full text |Cite
|
Sign up to set email alerts
|

Variations in infectivity of indigenous rhizobial isolates of some soils in the rainforest zone of Nigeria

Abstract: Nodule formation in legumes is a process that starts with root infection by rhizobia. The present study assessed the population and infectivity of the indigenous rhizobial strains in rainforest soils of Nigeria. Soils were collected from three sites -IdiAyunre, Orile-Ilugun (OI) and the University of Ibadan Teaching and Research Farm (UITRF) -and analysed for physico-chemical properties and rhizobial population. Soybean varieties TGx1448-2E and TGx1456-2E and a cowpea variety IT89KD-288 were planted as trap cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The present work indicated that all isolates including the uninoculated control produced the lowest mean NN and NDW in all genotypes at Babile. This was probably due to low rhizobial population in this site (Ojo et al 2015) and this consequently reduced the nodule formation. Low nodulation formation might be also attributed to the prevailed adverse environmental condition at Babile site (Hungria et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The present work indicated that all isolates including the uninoculated control produced the lowest mean NN and NDW in all genotypes at Babile. This was probably due to low rhizobial population in this site (Ojo et al 2015) and this consequently reduced the nodule formation. Low nodulation formation might be also attributed to the prevailed adverse environmental condition at Babile site (Hungria et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Soil samples were analysed for pH in water (1:1) as outlined in IITA (1982), soil organic matter using wet dichromate acid oxidation method (Nelson and Sommers, 1982), total nitrogen using Kjeldahl analytical method (Bremmer and Mulvaney, 1982), available phosphorus using Bray-1 method (Bray and Kurtz, 1945), particle size using Bouyoucus hydrometer method (Okalebo et al, 1993), exchangeable Mg, Ca, K and Na extracted using neutral 1M ammonium acetate and determined with spectrophotometer (Okalebo et al, 1993). The rhizobial population count of the three locations was determined as described Ojo et al (2015). The soil biological, chemical and physical characteristics of the three locations are presented in Table 1.…”
Section:  Methods  Location Climates and Soils Of The Experimentalmentioning
confidence: 99%
“…Studies on indigenous rhizobia for N fixing efficiency in soyabean in the forest transition zone of Nigeria are at best scanty. Ojo et al (2015) selected three indigenous rhizobial strains that are highly infective on soybean in the forest transition zone of Nigeria but information on their N fixation efficacy was lacking.…”
Section:  Introductionmentioning
confidence: 99%
“…Therefore, soils have been depleted due to a continuous cropping without soil replenishment as consequence of population pressure (Bashagaluke, 2015). In that case, crop yield depends upon N fixation by native rhizobia that are not always effective (Ojo et al, 2015) thus obtaining low yields, estimated at 0.5 t ha -1 (FAO, 2018).…”
Section: Introductionmentioning
confidence: 99%